A multi photodiode balanced detection technique for spectral amplitude coding OCDMA systems - Ahmed M., Alhassan; Nasreen, Badruddin; Mohamad Naufal, Mohamad Saad, Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org